A new system for Integral community cardiac rehabilitation based on technological platforms for the Lifestyle Change Supporting System - Gimenez, G.; Montagud, V.; Salvador, A.; Guixeres, J.; Villaescusa, F. J.; Saiz, J.; Merce, S.; Rodriguez, R.; Gomis-Tena, J.; Ferrero, J. M.; Sancho-Tello, M. J. (2006 Computers in Cardiology, 2006)
The main goal of this work was to design, develop and test a new system for Integral community cardiac rehabilitation phase III (CR-III) based on technological platforms for the LCSS's (Lifestyle Change Supporting System). The system has the following characteristics: personalized cardiac rehabilitation program, automatic support in establishing and modifying care program, risk factor ,monitoring access for the patients, intensive cardiac monitoring with automatic alarms, support self- care programs and continuous information of the therapy results. The LCSS is based on a Control and decision support system (tablet-PC). The system introduces the data for the session on the personal PDA of patient through a Wifi (802.11 b) connection. The PDA software works as a personal trainer of the patient, motivating and guiding the patient in his rehabilitation. The biomedical sensors are located on the chest and 6 ECG signals in non-standard leads are recorded during the exercise. Alarm warnings are induced when an ECG frequency higher than the maximal programmed by the system is detected, when an increment or decrement of ST segment is observed and when ectopic activity is detected.